The effect of physical exercise on Chinese college students’ mental sub-health: the mediating role of mental resilience and the moderating role of self-efficacy - Zhang, Shuaishuai (Frontiers in Psychology, 2025)
ObjectivesThis study aimed to explore the influence mechanism of physical exercise (PE) on the mental sub-health (MSH) of Chinese college students, elucidate the mediating pathway of mental resilience (MR) between exercise behavior and psychological state, and test the moderating effect of self-efficacy (SE). This research provides a theoretical basis for optimizing mental health intervention strategies in colleges and universities.MethodsUtilizing the MSH section of the Adolescent Sub-health Multidimensional Rating Questionnaire (MSQA), along with the Physical Activity Rating Scale (PARS), the Resilience Scale for Chinese Adolescent (RSCA), and the General SE Scale (GSES), a survey was conducted 1,811 students across various academic levels.Results(1) PE did not exhibit a direct predictive effect on the MSH of college students; (2) PE affected the MSH of college students through the mediating effect of MR; (3) SE played a moderating role in the relationship between PE and MSH among college students, specifically manifested as follows: With the improvement of the SE levels, the reducing effect of PE on MSH intensified; the reducing effect of MR on MSH also intensified with increasing SE levels.ConclusionThere was a moderating mediating effect between PE and MSH among Chinese college students. MR served as the mediating factor in this relationship, and SE moderated this effect.